Analysis of Regional-Based Fisheries Potential Development Strategies in Papua - Halomoan Hutajulu; Rachmaeny Indahyani; Eko Joko Nugroho; Sri Damayanti Toding (West Science Interdisciplinary Studies, 2026)
Large capture-fisheries and aquaculture potential in Papua Province has yet to meet the reality of regional development based on fisheries, due to infrastructure gaps, limited value-added processing, weak institutions, and continuous external risks. This study assesses the regional-based fisheries potential development strategy in Papua Province to increase coastal community welfare without compromising resource sustainability. Secondary data from the period of 2003–2024 are combined with stakeholder inputs from surveys, interviews, and focus group discussions and analyzed by using a SWOT framework supported by IFAS–EFAS weighting to identify strategic priorities. The mean IFAS score revealed that internal strengths (3.27) outweighed weaknesses (1.53), largely attributed to abundant fish resources, emerging fishing/processing technologies, government support, market potential, and local wisdom of coastal areas. Results from EFAS revealed that the mean opportunities (3.16) outweigh threats (1.81), particularly export demand, progress in technology, government programs, and digital marketing prospects, although illegal fishing, overfishing pressures, climate variability, and conflict over fishing grounds remained the key concerns. The position here is in the first quadrant, denoting an area where the fishery can grow well and indicates the need to focus more on Strength-Opportunity (SO) plans involving the optimization of export-directed manufacturing, the enhancement of fish processing facilities to increase value addition to fish, and the use of e-commerce and online marketing, as well as the use of local economic institutions to improve fish distribution, and the development of networks based on local culture to ensure superior processed fish products.